2015
DOI: 10.1021/acsnano.5b05043
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light-Activatable Microneedle System for Treating Superficial Tumors by Combination of Chemotherapy and Photothermal Therapy

Abstract: Because of the aggressive and recurrent nature of cancers, repeated and multimodal treatments are often necessary. Traditional cancer therapies have a risk of serious toxicity and side effects. Hence, it is crucial to develop an alternative treatment modality that is minimally invasive, effectively treats cancers with low toxicity, and can be repeated as required. We developed a light-activatable microneedle (MN) system that can repeatedly and simultaneously provide photothermal therapy and chemotherapy to sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
221
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(222 citation statements)
references
References 38 publications
1
221
0
Order By: Relevance
“…4,5 PTT utilizes heat generated from photothermal agents under near-infrared (NIR, λ=700−1,100 nm) light irradiation, 6,7 where the absorption of tissues is quite limited, to cause irreversible cellular damage and subsequent tumor destruction because cancer cells are more heat-sensitive than normal ones. 8 In PTT, photothermal agents are delivered to tumors either intravenously or intratumorally.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 PTT utilizes heat generated from photothermal agents under near-infrared (NIR, λ=700−1,100 nm) light irradiation, 6,7 where the absorption of tissues is quite limited, to cause irreversible cellular damage and subsequent tumor destruction because cancer cells are more heat-sensitive than normal ones. 8 In PTT, photothermal agents are delivered to tumors either intravenously or intratumorally.…”
Section: Introductionmentioning
confidence: 99%
“…3 With the development of tumor adjunctive therapy, the combined therapy of hyperthermia and chemotherapy has become a hot spot in related research fields. 4,5 Gold nanomaterials are a type of biomaterials that exhibit many excellent properties, such as easy molding, easy modification, and low toxicity, and they have always been used for near-infrared (NIR) light-induced photothermal therapy (PTT). 6,7 However, low tissue penetration and skin burning of NIR laser have seriously hindered its use.…”
Section: Introductionmentioning
confidence: 99%
“…For the treatment of skin cancers, microneedles are possible to arrive at tumor tissues, allowing for enhancing efficacy of therapeutic delivery. [22][23][24][25][26] For example, Wang et al reported the microneedle patch-assisted immunotherapy that delivers anti-PD-1 (aPD1) for the enhanced treatment of the skin cancer. 22 The microneedle patch with biocompatible hyaluronic acid and pH-sensitive dextran nanoparticles can painlessly penetrate the epidermis and become submerged in the interstitial fluid to efficiently deliver aPD1 to the tumor microenvironment, which inhibited tumor growth superior to those obtained with intratumor injection of the same dose.…”
Section: Introductionmentioning
confidence: 99%
“…20 Donnelly et al used silicon microneedle arrays to enhance skin penetration of porphyrin precursor 5-aminolevulinic acid (ALA) for photodynamic therapy, and in vivo experiments showed that microneedle puncture could reduce application time and ALA dose for high levels of the photosensitizer in skin. 23 Recently, Chen et al developed a multifunctional microneedle system with the combination of chemotherapy and photothermal therapy, [24][25] which consists of embeddable polycaprolactone (PCL) microneedles containing a photosensitive lanthanum hexaboride nanoparticles and an anticancer drug DOX. When applying microneedle system to treat mice bearing 4T1 breast tumors, the near-infrared light-activated heating and the DOX releasing behavior can be precisely controlled, and the microneedle-mediated synergistic therapy completely eradicated 4T1 tumors within 1 week.…”
Section: Introductionmentioning
confidence: 99%